2022
DOI: 10.1126/scitranslmed.abn0179
|View full text |Cite
|
Sign up to set email alerts
|

Axial alignment is a critical regulator of knee osteoarthritis

Abstract: Although osteoarthritis (OA), a leading cause of disability, has been associated with joint malalignment, scientific translational evidence for this link is lacking. In a clinical case study, we provide evidence of osteochondral recovery upon unloading symptomatic isolated medial tibiofemoral knee OA associated with varus malalignment. By mapping response correlations at high resolution, we identify spatially complex degenerative changes in cartilage after overloading in a clinically relevant ovine model. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…A detailed systematic review analyzed meniscectomy-induced OA in sheep [ 50 ], although the focus was not on subchondral bone alterations and no studies before 2010 were reported. Surgical OA induction was achieved via total medial (n = 2 studies) [ 3 , 12 ], total lateral (n = 3 studies) [ 11 , 13 , 29 ], and anterior partial medial (n = 2 studies) [ 43 , 44 ] meniscectomy, complete transection of the medial pars intermedia (i.e. MMT; n = 1 study) [ 12 ], and DMM (n = 1 study) [ 12 ] (Table 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed systematic review analyzed meniscectomy-induced OA in sheep [ 50 ], although the focus was not on subchondral bone alterations and no studies before 2010 were reported. Surgical OA induction was achieved via total medial (n = 2 studies) [ 3 , 12 ], total lateral (n = 3 studies) [ 11 , 13 , 29 ], and anterior partial medial (n = 2 studies) [ 43 , 44 ] meniscectomy, complete transection of the medial pars intermedia (i.e. MMT; n = 1 study) [ 12 ], and DMM (n = 1 study) [ 12 ] (Table 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 51,52 ] For the evaluation of the 3D microstructure of the subchondral bone, CT Analyzer software version 1.18 (Bruker) was used. In the osteochondral unit of each defect standardized volumes of interest (VOI) were defined to separate the “subchondral bone plate” and “subarticular spongiosa.” [ 52,53 ] VOIs had no intersections. Similar VOIs of the normal osteochondral unit were also examined in each trochlea, adjacent to the defects but not overlapping with them.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariate analyses were performed for all available bone or cartilage parameters of the samples as described previously. [52][53][54]56] Principal components analysis (PCA) with a correlation matrix routine, and non-parametric one-way analysis of similarities (ANOSIM) with Gower similarity index were used, and considering multiplicity issues, the Bonferroni-corrected p-values were reported. [57] Calculations were performed using GraphPad Prism 7.03 (GraphPad Software, San Diego, CA, USA) or Past v. 4.04.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the articular cartilage cannot repair itself, and once damaged, it will continue to deteriorate [ 126 ]. OA is the leading cause of disability worldwide [ 127 , 128 ]. The role and mechanism of articular chondrocytes (ACs) and BMSCs in cartilage repair have been extensively studied [ 129 , 130 , 131 ], and their mechanisms of action typically involve EVs.…”
Section: The Application Of Evs-loaded Hydrogels In Disease Treatmentmentioning
confidence: 99%